FACTORS INFLUENCING THE OCCURRENCE OF HYPERTROPHIC SCARS AMONG POSTOPERATIVE PATIENTS IN GARUT, INDONESIA - Andri Nugraha; Rizal Chaidir; Urip Rahayu; Santi Rinjani (Belitung Nursing Journal, 2017)
Background: Hypertrophic scar causes physical and psychological problems. Thus, understanding the factors related to the occurrence of hypertrophic scar tissue is needed. Little is known about its influencing factors in Indonesia, especially in Garut. Objective: This study aims to examine the relationships between hypertrophic scar and its influencing factors, and identify the most dominant factor of the occurrence of hypertrophic scars. Methods: This was an observational case control study using retrospective approach in Polyclinic of Surgery of Regional Public Hospital of dr. Slamet of Garut Regency. There were 40 samples recruited in this study by purposive sampling, which was divided to be case group (20 patients) and control group (20 patients). Data were collected using Stony Brook Scar Evaluation Scale by observation and documentation of the medical records of patients. Data were analyzed using logistic regression analysis. Results: Findings indicated that there were significant relationships between the surgical wound infection (p = 0.02), family history (p = 0.026), and type of suture (p = 0.043) with the occurrence of hypertrophic scars. The most dominant factor on the occurrence of hypertrophic scars was type of suture, acid polyglactin 910. The variables that had no significant relationships with the occurrence of hypertrophic scar tissue were age (p = 0.34), area of surgical wound (p = 0.177), and smoking habit (p = 0.479). Conclusion: There were significant relationships between infection of surgical wound, genetic history, the type of suture, and the occurrence of hypertrophic scar tissue. The most dominant factor that influenced the occurrence of hypertrophic scar tissue was the type of suture. Therefore, it is suggested to health professionals to modify the using of acid polyglactin 910 sutures, and nurses particularly need to provide the information regarding the family history and genetic-related hypertrophic scar, and prevent the infection of surgical wound after operation.